(untitled) (Fiep Bulletin - online, 2020)
Abstract: This study aimed to search scientific data to verify the action of physical exercise as an effective non-pharmacological treatment for sleep quality. This is a research that used the theoretical technical procedures of non-systematic literature review, by searching for articles in the Pubmed, Scielo and Medline databases. It was concluded that physical exercise is healthy in the quality of sleep, being advantageous to practitioners and can be used as a therapeutic treatment alone or as an adjunct in the treatment of sleep disorders.